Anthocyanins/anthocyanidins and colorectal cancer: What is behind the scenes?. Issue 1 (2nd January 2019) - de Sousa Moraes, Luís Fernando; Sun, Xiaofei; Peluzio, Maria do Carmo Gouveia; Zhu, Mei-Jun
ABSTRACT: Colorectal cancer (CRC) is one of the most common cause of cancer death. Phytochemicals, especially anthocyanins/anthocyanidins (A/A), have gathered attention of the scientific community owing to their anti-inflammatory, antioxidant, and cancer-inhibitory properties. In this review, we discussed the possible mechanisms whereby A/A exhibit intestinal anticarcinogenic characteristics. Anthocyanins/anthocyanidins inhibit the pro-inflammatory NF-κB pathway, attenuate Wnt signaling and suppress abnormal epithelial cell proliferation. In addition, A/A induce mitochondrial-mediated apoptosis and downregulate Akt/mTOR (mammalian target of rapamycin) pathway. Furthermore, activation of AMP-activated protein kinase (AMPK) and sirtuin 1 (SIRT1) also contributes to the anti-carcinogenic effects of A/A. Finally, downregulation of metalloproteinases (MMPs) by A/A inhibits tumor invasion and metastasis. In conclusion, A/A exert their anti-tumor effects against colorectal carcinogenesis via multiple mechanisms, providing insights into the use of A/A as a natural chemopreventive intervention on major colorectal carcinogenesis.